An ecological approach to hearing-health promotion in workplaces. (4th May 2017) - Reddy, Ravi; Welch, David; Ameratunga, Shanthi; Thorne, Peter
Abstract: Objective : To develop and assess use, acceptability and feasibility of an ecological hearing conservation programme for workplaces. Design : A school-based public health hearing preservation education programme (Dangerous Decibels®) was adapted for workplaces using the Multi-level Approach to Community Health (MATCH) Model. The programme was delivered in small manufacturing companies and evaluated using a questionnaire before the training and at one week and two-months after training. Study sample : Workers ( n  = 56) from five small manufacturing companies were recruited. Results : There was a significant improvement in knowledge, attitudes and behaviour of workers at the intrapersonal level; in behaviour motivation and safety culture at the interpersonal and organisational levels; and an overall improvement in hearing-health behaviour after two months post-intervention. Conclusions : The developed programme offers a simple, interactive and theory-based intervention that is well accepted and effective in promoting positive hearing-health behaviour in workplaces.